Adsorption of doxorubicin on citrate-capped gold nanoparticles: insights into engineering potent chemotherapeutic delivery systems. Issue 46 (9th November 2015) - Curry, Dennis; Cameron, Amanda; MacDonald, Bruce; Nganou, Collins; Scheller, Hope; Marsh, James; Beale, Stefanie; Lu, Mingsheng; Shan, Zhi; Kaliaperumal, Rajendran; Xu, Heping; Servos, Mark; et al.
Abstract : Doxorubicin adsorption onto citrate-capped gold nanoparticles is mainly governed by cationic–π and carbonyl coordination chemistry. Abstract : Gold nanomaterials have received great interest for their use in cancer theranostic applications over the past two decades. Many gold nanoparticle-based drug delivery system designs rely on adsorbed ligands such as DNA or cleavable linkers to load therapeutic cargo. The heightened research interest was recently demonstrated in the simple design of nanoparticle-drug conjugates wherein drug molecules are directly adsorbed onto the as-synthesized nanoparticle surface. The potent chemotherapeutic, doxorubicin often serves as a model drug for gold nanoparticle-based delivery platforms; however, the specific interaction facilitating adsorption in this system remains understudied. Here, for the first time, we propose empirical and theoretical evidence suggestive of the main adsorption process where (1) hydrophobic forces drive doxorubicin towards the gold nanoparticle surface before (2) cation–π interactions and gold–carbonyl coordination between the drug molecule and the cations on AuNP surface facilitate DOX adsorption. In addition, biologically relevant compounds, such as serum albumin and glutathione, were shown to enhance desorption of loaded drug molecules from AuNP at physiologically relevant concentrations, providing insight into the drug release and in vivo stability of such drug conjugates.